Background: More than 20 years ago Lichtenstein popularized the technique of placing the polypropylene mesh for hernia repair groin, using this technique regardless the characteristics of the same, making a stress-free repair. Our experience with the Lich - Viola, Marcelo; Olivera, Eduardo; Curi, Jorge; Moure, Luis; Tchekmedyian, Vartan; Estapé, Gonzalo (Cirugía del Uruguay, 2005)
Background: Over 20 years ago Líchtenstein rendered popular a technique, which consisted of placing a polypropy/ene mesh far repair of inguinal hernia, applying this technique regardless of its characteristics and thus enabling repair procedures free from tension. Our experience with Líchtenstein, s technique begins in 1993 with two preliminary series in the years 1994 and 1998.